Applications of MOFs as Luminescent Sensors for Environmental Pollutants. Issue 22 (26th February 2021) - Yang, Guo‐Li; Jiang, Xiao‐Lei; Xu, Hang; Zhao, Bin
Abstract: The environmental pollution has become a serious issue because the pollutants can cause permanent damage to the DNA, nervous system, and circulating system, resulting in various incurable diseases, such as organ failure, malformation, angiocardiopathy, and cancer. The effective detection of environmental pollutants is urgently needed to keep them far away from daily life. Among the reported pollutant sensors, luminescent metal–organic frameworks (LMOFs) with tunable structures have attracted remarkable attention to detect the pollutants because of their excellent selectivity, sensitivity, and recyclability. Although lots of metal–organic framework (MOF)‐based luminescent sensors have been summarized and discussed in previous reviews, the detection of environmental pollutants, especially radioactive ions and heavy metal ions, still have not been systematically presented. Here, the sensing mechanisms and construction principles of luminescent MOFs are discussed, and the state‐of‐the‐art MOF‐based luminescent sensors of environmental pollutants, including pesticides, antibiotics, explosives, VOCs, toxic gas, toxic small molecules, radioactive ions, and heavy metal ions are highlighted. This comprehensive review may further guide the development of luminescent MOFs and promote their practical applications for sensing environmental pollutants. Abstract : Luminescent MOFs have attracted remarkable attention to detect environmental pollutants because of their excellent selectivity, sensitivity, and recyclability. In this review, the sensing mechanisms and construction principles of luminescent MOFs are discussed, and the state‐of‐the‐art luminescent MOF‐based sensors of environmental pollutants, including pesticides, antibiotics, explosives, VOCs, toxic gas, toxic small molecules, radioactive ions, and heavy metal ions are highlighted.